2009
DOI: 10.1080/02713680902963167
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Polytetrafluoroethylene Membrane Alters Tissue Response to Implanted Ahmed Glaucoma Valve

Abstract: Encapsulating the aqueous outflow pathway with a porous membrane produces a more vascular tissue response and thinner fibrous capsule compared with a standard glaucoma implant plate. Enhanced vascularity and a thinner fibrous capsule may reduce aqueous outflow resistance and improve long-term glaucoma implant performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…Capsules also had more dilated vessels throughout the fibrous capsule. These results were in agreement with previous studies with histopathological findings for a glaucoma drainage device modulated by various adjunctive treatments [28,29,30]. Park et al [28] evaluated the effects in rabbits of topical cyclosporine on the function of filtering blebs after glaucoma drainage implant surgery.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Capsules also had more dilated vessels throughout the fibrous capsule. These results were in agreement with previous studies with histopathological findings for a glaucoma drainage device modulated by various adjunctive treatments [28,29,30]. Park et al [28] evaluated the effects in rabbits of topical cyclosporine on the function of filtering blebs after glaucoma drainage implant surgery.…”
Section: Discussionsupporting
confidence: 82%
“…Flow resistance through the implant capsule was significantly lower in the study group [28]. DeCroos et al [29] reported that encapsulating tissue was altered by an expanded polytetrafluoroethylene membrane in AGV surgery, led to greater vascular tissue response and a thinner fibrous capsule compared with a standard glaucoma implant plate. Sahiner et al [30] examined histological findings in rabbits with fibrous capsules around a slow-release antifibrotic drug-coated glaucoma device.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work from our group demonstrated that the PRIME-Ahmed promoted a thinner fibrous capsule and increased vascularity adjacent to the implant when compared to unmodified Ahmed valves implanted in rabbits (46.4 ±10.8 μm versus 94.9 ± 21.2 μm, p < 0.001). 27 A thinner, more vascular capsule may decrease outflow resistance in vivo significantly enough to improve long-term intra-ocular pressure control. However, prior to implantation and in vivo study, it is important to assess how much serial resistance is added by porous membrane enclosure of a GDD outflow tract.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work demonstrated that PRIME-Ahmed implanted into the rabbit eye stimulates a thinner fibrous capsule and increased surrounding vascularity compared to implanted unmodified Ahmed valve. 27 The thinner, more vascular capsule promoted by the PRIME-Ahmed may improve longterm absorption of aqueous fluid through decreased resistance to fluid flow in vivo.…”
Section: Fluid Dynamics Of the Eptfe Modified Ahmed Implantmentioning
confidence: 99%
See 1 more Smart Citation